Evaluation of bisphenylthiazoles as a promising class for combating multidrug-resistant fungal infections. - Mohamed Hagras (Public Library of Science (PLoS), 2021)
To minimize the intrinsic toxicity of the antibacterial agent hydrazinyloxadiazole 1, the hydrazine moiety was replaced with ethylenediamine (compound 7). This replacement generated a potent antifungal agent with no antibacterial activity. Notably, use of a 1,2-diaminocyclohexane moiety, as a conformationally-restricted isostere for ethylenediamine, potentiated the antifungal activity in both the cis and trans forms of N-(5-(2-([1,1'-biphenyl]-4-yl)-4-methylthiazol-5-yl)-1,3,4-oxadiazol-2-yl)cyclohexane-1,2-diamine (compounds 16 and 17). Both compounds 16 and 17 were void of any antibacterial activity; nonetheless, they showed equipotent antifungal activity in vitro to that of the most potent approved antifungal agent, amphotericin B. The promising antifungal effects of compounds 16 and 17 were maintained when assessed against an additional panel of 26 yeast and mold clinical isolates, including the Candida auris and C. krusei. Furthermore, compound 17 showed superior activity to amphotericin B in vitro against Candida glabrata and Cryptococcus gattii. Additionally, neither compound inhibited the normal human microbiota, and both possessed excellent safety profiles and were 16 times more tolerable than amphotericin B.